Serum Ferritin and Gestational Diabetes Mellitus: A Case Control Study (Ibrahim Cardiac Medical Journal, 2013)
Ibrahim Cardiac Medical Journal 2011; 1(2): 15-19 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13546